PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING DENGAN TEKNIK CROSSWORDS PUZZLE DALAM MENINGKATKAN HASIL BELAJAR SISWA POKOK BAHASAN MATRIKS KELAS X PROGRAM KEAHLIAN AKUNTANSI SMK NEGERI 1 JEMBER - M, Rafiantika; Dafik, D; Susanto, S (Kadikma, 2013)
Abstract.Quantum Teaching is real life learning strategy with relevances social nuances. Quantum Teaching consists of four steps, namely Tumbuhkan (Motivate), Alami (Do), Namai (Symbolize), Demonstrasikan (Demonstrate), Ulangi (Repeat) (TANDUR, for short). The research purpose is to analyze thestudents learningachievement and activities. The research design is Classroom Action Research (CAR). It consists of four stages. Plan, implementation, observation, and reflection. The research was done in two cycles. The result shows that the percentage of student learning achievement and activities respectively increase from cycle I to cycle II, namely 75% to83,33% and 70,27 % to 83,55%. It can be concluded that the application of Quantum Teaching with Crosswords puzzle technique can effectively improve studentlearning achievement as well as their activities. Key Words: Quantum Teaching,Studentlearning achievement, and activities